Birthday girl - Murakami, Haruki (Gurgaon Penguin Random House, 2019)
She waited on tables as usual that day, her twentieth birthday. She always worked Fridays, but if things had gone according to plan on that particular Friday, she would have had the night off. One rainy Tokyo night, a waitresss uneventful twentieth birthday takes a strange and fateful turn when shes asked to deliver dinner to the restaurants reclusive owner. Birthday Girl is a beguiling, exquisitely satisfying taste of master storytelling, published to celebrate Murakamis 70th birthday....
Keywords: Birthdays; Japanese fiction